2014
DOI: 10.1039/c4ja00124a
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mass dependent and mass independent selenium isotope variability in black shales

Abstract: The measurement of selenium isotope ratios is of increasing interest for understanding redox conditions in present and past surface environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…Over a measurement period of about 30 minutes average Se signals of ~1-2 V were observed for 500 ng Se, which is slightly higher compared to literature data for other TIMS measurements [13]. Current ICP-MS-based methods use similar to significantly less amounts of Se [4,18].…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…Over a measurement period of about 30 minutes average Se signals of ~1-2 V were observed for 500 ng Se, which is slightly higher compared to literature data for other TIMS measurements [13]. Current ICP-MS-based methods use similar to significantly less amounts of Se [4,18].…”
Section: Resultsmentioning
confidence: 64%
“…However, a large number of isobaric interferences like Ar 2 , ArCl, Ge, NiO, and hydrides formed with Ar 2 , As, Ge, and Se require the application of on-peak zero corrections [19]. The details of this interference correction differ between the published studies and may be the reason for the observed discrepancies in the published Se isotope values of rock standards of up to 0.5 ‰ in δ 82/76 Se [4]. Furthermore, different ICP-MS instruments and HG systems result in different intensities of the interfering signals.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Se isotope ratios bear the potential to show historic redox changes in the ancient oceans through assessment of the Se isotopic signatures recorded in ancient sedimentary rocks [136]. Further, studies on mass independent fractionation of Se in accordance with mass independent fractionation of S isotopes has gained interest during the last years [137]. Se isotopes and Se isotopic fractionation in the context of the study of the mineral and trace element metabolism in humans was comprehensively discussed recently by Walczyk [84].…”
Section: Fig 4 Distribution Of Publications Between 2010 and 2015 Fomentioning
confidence: 99%
“…Since 2007, isotope pattern deconvolution involving enriched isotopes in biological entities has been successfully applied for e.g., 57 Fe in cucumber plants [164]; 74 Se and 77 Se in lactating rats [165] and 77 Se in human serum [166]; 135 Ba and 137 Ba in fish tissues [167,168]; 67 Zn and 70 Zn in rat brain thin sections [169,170]. The methodology has also been picked up for forensic and environmental applications such as the authentication of explosives tagged with a dual isotope spike of tin ( 117 Sn and 119 Sn) [171] or the analyses of platinum ( 194 Pt) in environmental samples [172].…”
Section: Isotopic Labeling Using Enriched Stable Isotopes (Extrinsic mentioning
confidence: 99%